Penerapan Finite State Automata Pada Simulasi Vending Machine Water and Ice Cube - Nadia Annisa Maori; Oki Setiono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The need for fluids in the human body when in hot weather is increasing because hot weather can make humans dehydrated. Dehydration is a condition in which the body loses too much fluid and electrolytes compared to what enters the body (Sari & Nindya, 2017). Beverage sellers who are on the side of the road can help meet water needs. However, the existence of drink sellers on the side of the road often disrupts traffic and the cleanliness and quality of the product is not guaranteed. Based on the problems above, vending machines can be used for easy consumer access because they are easy and fast to use, and can be available 24 hours. Beverage vending machines are designed using the finite state automata concept as a program flow. The result is a proven FSA that can be applied to beverage vending machines easily and according to the grooves designed in the FSA diagram. Input and output can be accepted and rejected according to the FSA diagram that has been determined in the study. This is based on the results of tests that have been carried out using JFLAP.